Аналіз гранулометричного складу ґрунтів сільськогосподарських земель поблизу відвалу розкривних порід - Рудаков, О. Л.; Максимова, Н. М.; Чушкіна, І. В. (Національний університет «Львівська політехніка», 2022)
On the basis of laboratory studies by the pipette method it was found that in the vast majority of soils of agricultural lands are classified as loamy, and when approaching the zone of influence of the existing heap of overburden – as sandy. As a result of field research it was found that an additional factor in the restoration of air erosion of the surface is the course of suffusion, the formation of dips on the earth's surface. The performed field and laboratory works testify to the expediency of further research, in particular, aimed at checking the presence of inhibition of cellulosolytic activity of fertile soils in the area of influence of man-made embankments.